Evaluating the efficiency of major container shipping companies: A framework of dynamic network DEA with shared inputs - Chao, Shih-Liang; Yu, Ming-Miin; Hsieh, Wei-Fan (Transportation research. Part A, Policy and practice, 2018)
•We decomposed the process for producing shipping service of a container carrier in multiple periods.•The annual efficiency and division efficiency of major container carriers were measured.•The optimal solution for sharing common inputs and adjusting owned fleet capacity was also found from our model. Taking advantage of a dynamic network data envelopment analysis (DNDEA), this study proposes a model decomposing shipping service production for a container shipping company (CSC) into two processes. Meanwhile, multiple evaluation periods are linked by carry-over activity. The fleet capacity of a CSC is separated into owned fleet capacity (OFC) and chartered-in fleet capacity, which are defined as carry-over activity and specific input, respectively. The efficiency of 13 major global CSCs is empirically evaluated based on a dataset covering a period from 2013 to 2015. The scores for company efficiency and division efficiency of each CSC are measured and examined. In addition, the optimal solution for sharing common inputs and adjusting OFC is also found from our model.